2015
DOI: 10.1103/physrevb.92.125434
|View full text |Cite
|
Sign up to set email alerts
|

Role of metastable charge states in a quantum-dot spin-qubit readout

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21276979&lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?action=rtdoc&an=21276979&lang=fr READ THESE TERMS AND CONDITIONS CAREFULLY BEFORE USING THIS WEBSITE.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en Vous avez des questions? Nous pouv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Second, it has not been demonstrated whether the signal lifetime could also be enhanced via this charge mapping process. It was reported that the expected signal enhancement was not observed in one case [20], raising doubts as to whether this process can be achieved with high fidelity. Third, the mechanisms that limit the lifetimes of the metastable states are still not understood, and a comprehensive comparison of various alternative mapping schemes is lacking.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, it has not been demonstrated whether the signal lifetime could also be enhanced via this charge mapping process. It was reported that the expected signal enhancement was not observed in one case [20], raising doubts as to whether this process can be achieved with high fidelity. Third, the mechanisms that limit the lifetimes of the metastable states are still not understood, and a comprehensive comparison of various alternative mapping schemes is lacking.…”
Section: Introductionmentioning
confidence: 95%
“…The two-electron QD-D system can be thought of as a singlet-triplet (ST) qubit [22][23][24] in an effective double QD configuration [25] where only one of the QDs is connected directly to a charge reservoir [21]. This configuration produces latching (or hysteresis [26]) of the QD-D charge state that can be harnessed to enhance the charge detection [18][19][20] in two ways.…”
Section: Introductionmentioning
confidence: 99%
“…Spin qubits, due to their long coherence time, have attracted much interest in the past few years. One key requirement of spin qubits is to establish a spin-to-charge conversion mechanism by which spin states can be read out using a charge sensor [24][25][26][27][28][29]. The most widely used means is spin blockade [27,28], which maps triplet and singlet states to different charge distributions across the double quantum dot (DQD).…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used means is spin blockade [27,28], which maps triplet and singlet states to different charge distributions across the double quantum dot (DQD). Recently an alternative mechanism has been reported [25,26], which maps the triplet state to a metastable charge state with one electron more or less than the singlet state.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we utilize an energy selective readout technique relying on relaxation of the metastable triplet state in the (1,1) configuration when pulsed into the (2,0) region. The method has been previously demonstrated in a time-averaged fashion [24][25][26]; however, we employ threshold discrimination analysis (cf., singlespin readout [27]) for single-shot readout with fidelity greater than 98%-close to fault tolerant thresholds for surface-code quantum computation [28].The device shown in Fig. 1 was fabricated using scanning tunneling microscope hydrogen lithography.…”
mentioning
confidence: 99%